2020
DOI: 10.3390/ijms21207547
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Ethyl Ester Protects In Vitro-Maturing Bovine Oocytes against Oxidative Stress Induced by Subsequent Vitrification/Warming

Abstract: This study aimed to examine whether the addition of glutathione ethyl ester (GSH-OEt) to the in vitro maturation (IVM) medium would improve the resilience of bovine oocytes to withstand vitrification. The effects of GSH-OEt on spindle morphology, levels of reactive oxygen species (ROS), mitochondrial activity and distribution, and embryo developmental potential were assessed together with the expression of genes with a role in apoptosis (BAX, BCL2), oxidative-stress pathways (GPX1, SOD1), water channels (AQP3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…1E , chrysin notably increased the proportion of apoptotic cells. Bax is a pro-apoptotic protein that leads to cell death, whereas Bcl-2 is an anti-apoptotic protein that promotes cell survival ( 21 ). Western blotting revealed that the treatment of HEC-1A and Ishikawa cells with chrysin for 48 h increased the level of Bax and decreased the expression of Bcl-2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E , chrysin notably increased the proportion of apoptotic cells. Bax is a pro-apoptotic protein that leads to cell death, whereas Bcl-2 is an anti-apoptotic protein that promotes cell survival ( 21 ). Western blotting revealed that the treatment of HEC-1A and Ishikawa cells with chrysin for 48 h increased the level of Bax and decreased the expression of Bcl-2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro maturation (IVM) procedure followed has been described previously 49 . Briefly, ovaries from slaughtered postpubertal heifers (12–18 months old) were transported from a local slaughterhouse to the laboratory in saline solution (0.9% NaCl) at 35–37 °C within 2 h. Immature cumulus-oocyte complexes (COCs) were aspirated from 3 to 8 mm follicles using an 18-gauge needle attached to a 5 mL syringe.…”
Section: Methodsmentioning
confidence: 99%
“… 27 , 28 Therefore, the effect of antioxidants on oocytes and embryo following vitrification has been extensively studied; supplementation of culture medium of vitrified‐warmed oocytes or embryos with melatonin, glutathione ethyl‐ester, N‐acetyl cysteine, α‐tocopherol, or coenzyme Q reduced ROS levels and improved oocyte viability as well as embryo development in equine, cows, and mice. 6 , 29 , 30 , 31 , 32 In addition, supplementation of vitrified‐warming solution with acetyl‐L‐carnitine, N‐acetyl‐cysteine, and lipoic acid improved the cell number of the blastocysts and fetal development in mice. 33 Furthermore, addition of vitamin E to the culture medium of vitrified‐warming ovarian tissue improved oocyte and subsequent blastocyst stage development.…”
Section: Antioxidants Protect Vitrified‐warmed Oocytes and Embryosmentioning
confidence: 99%
“…A study in humans showed that vitrified‐warmed oocytes have low ATP levels and mitochondrial membrane potential, abnormal mitochondrial configuration and localization, and ROS and intracytoplasmic Ca levels. 4 , 5 , 6 In addition, transition electron microscope revealed that mitochondria in vitrified‐warmed embryos had swollen morphology. 7 , 8 , 9 In our studies based on porcine oocytes, bovine eight‐cell stage and blastocyst stage embryos, ATP content, mitochondrial genome integrity and developmental ability in cryopreserved samples was low compared with those fresh counterparts.…”
Section: Introductionmentioning
confidence: 99%